(untitled) (Revista Latino-Americana de Enfermagem, 2010)
This study aimed to analyze the occurrence of skin toxicity caused by drugs used in the protocol of neoadjuvant and adjuvant chemotherapy among women with breast cancer. Patient records of 72 women who were subject to this therapy between 2003 and 2006 were assessed. Of the 558 cycles of chemotherapy, 152 adverse events were registered. There were 37 registrations of dermatological toxicity, of those, 20 were extravasations that affected 17 women. Nine reports of hardened local injury, local fibrosis, pain, and hyperemia were registered during neoadjuvancy. In adjuvancy, among the 11 extravasations registered there were reports of hardened local injury, fibrosis and local pain. Lack of follow-up records for both periods was observed. Registration of the events and reports by the nursing team are essential to monitor the sites of venous puncture during the chemotherapy treatment, besides measuring and making a photographic record of the site.